Ethanol mediated photoinduced reversible adsorption of methylene blue on nano titanium dioxide. - Jaliya Manuda, K.R.; Tillekaratne, A.; Jayasundara, Dilushan R. (Research on Chemical Intermediates, Springer, 2022)
The photocatalytic activity of nano titanium dioxide (TiO2) on aqueous commercial dyes such as methylene blue (MB) is widely reported in literature. However, similar photocatalytic studies carried out in non-aqueous solvents are scarce. A series of ethanolic MB solutions were irradiated by ultraviolet (UV) radiation in the presence of TiO2. Effects of exposure time, adsorbate concentration and dispersion medium were considered. UV–Visible (UV–Vis) spectrophotometry and Fourier transform infrared spectroscopy were employed for characterization. The results show that photocatalytic activity of TiO2 on MB strongly depends on the dispersion medium. Contrary to the photocatalytic degradation of dyes that is generally seen in the aqueous medium, we report for the first time a photoinduced reversible adsorption of MB on nano TiO2 in ethanol. We further demonstrate that our newly reported phenomenon is mediated by the photocatalytic degradation of ethanol of which its resultant intermediates temporarily modify the nano TiO2 surface. Hence, our experimental findings differentiate photoinduced adsorption and photocatalytic degradation, where nano TiO2 acts an adsorbent and a catalyst, respectively.
Keywords: Photocatalysis, Adsorption, Nano titanium dioxide, Methylene blue, Ethanol